"No one wants to look after the fibro patient". Understanding models, and patient perspectives, of care for fibromyalgia: reviews of current evidence. Issue 8 (August 2020) - Doebl, Stefanie; Macfarlane, Gary J.; Hollick, Rosemary J.
Abstract : Abstract: Fibromyalgia is a common and complex long-term pain condition. Despite advancements in our understanding and treatment of fibromyalgia, patients report patchy health care provision and frustrating journeys through the health care system. To inform how best to deliver care, we undertook 2 narrative reviews examining existing evidence on (1) models of care for fibromyalgia and (2) patients' experiences, preferences, and unmet needs regarding their health care. Seven databases were systematically searched. Quantitative data was narratively synthesised and qualitative data thematically analysed. No evidence-based model of care covering the patient journey through the entire health care system was identified. Limited evidence suggests no clear benefit for ongoing care in secondary care settings. Patients with fibromyalgia report difficult interactions with the health care system that might equally be expressed by those with other long-term conditions, such as inconsistent and poorly coordinated care. However, they also face unique problems; fibromyalgia was often not viewed as a real condition, resulting in difficult encounters with health care staff, in particular not feeling believed or listened to. Significant delays in diagnosis were commonplace. Positive care experiences such as being listened to and shared decision-making made patients feeling better informed, well supported, and more satisfied. There is little evidence to inform how best to organise health care for patients with fibromyalgia and ensure care is delivered in a coordinated and consistent way. These findings provide a strong rationale for developing a new model of care for fibromyalgia.